2017
DOI: 10.1681/asn.2016121349
|View full text |Cite
|
Sign up to set email alerts
|

The Sorting Nexin 3 Retromer Pathway Regulates the Cell Surface Localization and Activity of a Wnt-Activated Polycystin Channel Complex

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is caused by inactivating mutations in (85%) or (15%). The ADPKD proteins encoded by these genes, polycystin-1 (PC1) and polycystin-2 (PC2), form a plasma membrane receptor-ion channel complex. However, the mechanisms controlling the subcellular localization of PC1 and PC2 are poorly understood. Here, we investigated the involvement of the retromer complex, an ancient protein module initially discovered in yeast that regulates the retrieval, sorting, and ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
0
20
1
Order By: Relevance
“…In addition, this study established the interaction of endogenous PC2 with endogenous VPS35, and interestingly reported increased levels of PC2 and PC1 at the bulk plasma membrane following retromer depletion. Although the study of Feng and colleagues did not include analysis of ciliary PC1 levels upon retromer knockdown (Feng et al, 2017), given that PC2 exists in complex with PC1 at the primary cilium, this result is in contrast to our finding that ciliary levels of PC1 are decreased in PKDknockout cells re-expressing PC2 p.I54A and p.I59A-myc. That said, it may be that the cell types used in this and our study have different trafficking requirements, and rely on the retromer complex to different extents for the internalisation and retrograde trafficking of polycystin proteins.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In addition, this study established the interaction of endogenous PC2 with endogenous VPS35, and interestingly reported increased levels of PC2 and PC1 at the bulk plasma membrane following retromer depletion. Although the study of Feng and colleagues did not include analysis of ciliary PC1 levels upon retromer knockdown (Feng et al, 2017), given that PC2 exists in complex with PC1 at the primary cilium, this result is in contrast to our finding that ciliary levels of PC1 are decreased in PKDknockout cells re-expressing PC2 p.I54A and p.I59A-myc. That said, it may be that the cell types used in this and our study have different trafficking requirements, and rely on the retromer complex to different extents for the internalisation and retrograde trafficking of polycystin proteins.…”
Section: Discussioncontrasting
confidence: 97%
“…As there exists no sequence similarity between the region in DENND4C and PC2 required for association with retromer (data not shown), it seems likely that architecture of the retromer complex as a whole affects interaction with both these proteins. In fact, while our manuscript was in preparation, it was demonstrated through the use of a tri-cistronic vector encoding VPS26, VPS29 and VPS35, that PC2 does indeed directly bind the retromer complex (Feng et al, 2017). In addition, this study established the interaction of endogenous PC2 with endogenous VPS35, and interestingly reported increased levels of PC2 and PC1 at the bulk plasma membrane following retromer depletion.…”
Section: Discussionmentioning
confidence: 55%
“…Sorting nexins anchor cargo proteins to membranes enriched in phosphatidylinositol‐3‐phosphate via their Phox homology (PX) domain (Figure 1c) and have been implicated in protein secretion 24 . Although no functions are currently described for SNX22, other members of this family, such as SNX3, are well studied and known to function in directing retromer‐mediated vesicle transport to the trans‐Golgi network, a conserved trafficking pathway that guides the retrieval, sorting, recycling, and retrograde transport of membrane receptors 25 . Phosphorylation within the PX domain of SNX3 abolishes PtdIns binding, resulting in cytosolic localisation 26 and exemplifying the modulation of SNX function by protein kinases.…”
Section: Resultsmentioning
confidence: 99%
“…Both Wnt signaling pathways have been proposed to have a link to ADPKD progression in animal models and human patients (20,21,(23)(24)(25). Hitherto, many reports have shown that renal cystic disease may result from dysregulation of the noncanonical Wnt pathway by disrupting Wnt/ Ca 2+ signaling and/or PCP processes in renal epithelial cells (23,(26)(27)(28)(29)(30)(31)(32). The roles of canonical Wnt signaling in pathogenesis of ADPKD remain to be unequivocally defined.…”
Section: Introductionmentioning
confidence: 99%